The Imaginary of Health Promotion in the everyday life of families in Primary Care - Juliana Chaves Costa; Rosane Goncalves Nitschke; Patrícia Fernandes Albeirice da Rocha; Betina Barbedo Andrade (Universidade Federal de Santa Maria, 2019)
Objective: to know the imaginary of Health Promotion of families in the Primary Health Care routine. Method: a qualitative, descriptive and exploratory study, conducted from August to November 2015 in a municipality in southern Brazil, in the light of the Comprehensive Sociology and Everyday Life of Maffesoli. Data were collected through semi-structured interviews with 19 participants and analyzed according to Schatzman and Strauss. Results: four categories emerged: Seeking health in daily life; Prioritize and Promote a better quality of life; Weaknesses of health promotion in the daily life of the Unified Health System (SUS); Potentialities of health promotion in SUS routine. Final Considerations: Participants point to behavior change and do not expand health issues beyond the health sector and lifestyle. However, they emphasize the desire to urge themselves in search of rights, as citizens and users of SUS.